Influence of selection on the probability of fixation at a locus with multiple alleles - A. D. J. Overall; D. Waxman (BMC Genomics, 2024)
Abstract Background Genes exist in a population in a variety of forms (alleles), as a consequence of multiple mutation events that have arisen over the course of time. In this work we consider a locus that is subject to either multiplicative or additive selection, and has n alleles, where n can take the values 2, 3, 4, $$…$$ … . We focus on determining the probability of fixation of each of the n alleles. For $$n = 2$$ n = 2 alleles, analytical results, that are ‘exact’, under the diffusion approximation, can be found for the fixation probability. However generally there are no equally exact results for $$n \ge 3$$ n ≥ 3 alleles. In the absence of such exact results, we proceed by finding results for the fixation probability, under the diffusion approximation, as a power series in scaled strengths of selection such as $$R_{i,j}=2N_{e}(s_{i}-s_{j})$$ R i , j = 2 N e ( s i - s j ) , where $$N_{e}$$ N e is the effective population size, while $$s_{i}$$ s i and $$s_{j}$$ s j are the selection coefficients associated with alleles i and j, respectively. Results We determined the fixation probability when all terms up to second order in the $$R_{i,j}$$ R i , j are kept. The truncation of the power series requires that the $$R_{i,j}$$ R i , j cannot be indefinitely large. For magnitudes of the $$R_{i,j}$$ R i , j up to a value of approximately 1, numerical evidence suggests that the results work well. Additionally, results given for the particular case of $$n = 3$$ n = 3 alleles illustrate a general feature that holds for $$n \ge 3$$ n ≥ 3 alleles, that the fixation probability of a particular allele depends on that allele’s initial frequency, but generally, this fixation probability also depends on the initial frequencies of other alleles at the locus, as well as their selective effects. Conclusions We have analytically exposed the leading way the probability of fixation, at a locus with multiple alleles, is affected by selection. This result may offer important insights into CDCV traits that have extreme phenotypic variance due to numerous, low-penetrance susceptibility alleles.